A Study on High-Frequency Induction Welding of TRIP 690 Tubes using Mechanical Tests and Computer Simulations - Okoroafor, Sydney (University of Waterloo, 2025)
The High-Frequency Induction Welding (HFIW) process is increasingly being adopted for manufacturing tubes used in hydroformed Advanced High Strength Steel (AHSS) components, specifically TRIP 690, in the automotive industry. This trend is driven by strict government climate legislation on automobiles that promotes the development of lightweight materials (AHSS) and efficient manufacturing techniques in the industry. Despite its advantages, the HFIW of TRIP 690 faces significant challenges, particularly the recurring issue of oxide inclusion defects. These defects are often undetectable by conventional tube mill inspection technologies and can only be identified through destructive mechanical testing. These defects also lead to poor mechanical properties and potential failures during complex loading scenarios like tube hydroforming. These oxide inclusion defects have not been explored in literature, leading to a critical knowledge gap in the HFIW of TRIP 690 that reduces the yield of high-quality TRIP 690 tubes during the HFIW process. This research aims to bridge the knowledge gaps associated with the HFIW of TRIP 690. It first investigates the influence of welding parameters and oxide inclusions on the mechanical properties of TRIP 690 tubes. Key findings indicate that the Ring Hoop Tensile (RHT) test yields reliable mechanical property data, revealing notable discrepancies when compared to traditional flat sheet data. The study also establishes that welding power and speed significantly affect Ultimate Tensile Strength (UTS), Uniform Elongation (UE), and fracture toughness. Optimal operating regions are identified through mechanical properties-process mapping, linking these properties to the mechanical properties-thermal process map for heat input and temperatures at the vee apex experienced in the vee region. Furthermore, the presence of oxide inclusions is shown to detrimentally impact mechanical performance, resulting in substantial reductions in UTS, elongation, and toughness. A preliminary mesoscale Finite Element Analysis (FEA) model demonstrates the potential to predict failure behavior in samples containing oxide inclusions through simulations. In addition, this research explores the thermal dynamics of the vee region during the HFIW process. A numerical model developed in COMSOL Multiphysics integrates the thermal modeling with experimental validation from tube mill trials, providing a comprehensive analysis of how critical parameters—such as heat flux, coil-to-weld point distance, and the thermophysical properties of TRIP 690—affect weld quality. Through this study useful tools have been developed that can aid in the optimization of HFIW of TRIP 690.
Keywords: COMSOL; TRIP steel; TRIP 690; high-frequency induction welding; HFIW; ring hoop tensile test; RHT test; tube making; automotive; body-in-white; Hydroforming; AHSS